Pengaruh tipe penggunaan lahan dalam membentuk komunitas semut dan layanan ekosistem yang diberikan - Muhammad Badrus Sholih; Damayanti Buchori; Idham Sakti Harahap; Akhmad Rizali (Perhimpunan Entomologi Indonesia, 2019)
Ants provide important ecosystem services such as predation and decomposition. The ecosystem services in different land-use systems will be influenced by the dominant ants species in those areas. The objectives of this study were to investigate the impact of land use types on ant community structure and to measure the ecosystem service provided by ants. The study was done in several land-use types in Jambi i.e. secondary forest, jungle rubber, rubber plantation, and oil palm plantation during April–Juni 2014. In each land-duse type, four plots were selected with a size of 50 m x 50 m for each plot. Each plot consisted of five subplots of 5 m x 5 m. In each plot, a tree was chosen for further observation on ant diversity and its ecosystem services. Ants were collected with the baiting method using Corcyra cephalonica larva that was laid on a plastic plate and put on the ground and on the tree stem. Ecosystem services were measured by observing the number of C. cephalonica larvae that were carried or removed by ants within a 1-hour observation. The results showed that the forest has the highest ant species richness than other land-use types. Land-use types have no impact on ant species richness but affected ants species composition. The highest removal C. cephalonica by ants was found in the secondary forest. Ants that played important role in ecosystem service in this study as predator were Achantomyrmex sp. 01, Aenictus sp.01, Carebara sp. 01, Tetramrium sp. 02, O. denticulata, Tetramorium sp. 03, Crematogaster sp. 02, A. gracilipes and Rhoptromyrmex sp.01.